Enhanced control of DFIG-based wind power plants to comply with the international grid codes - Mohseni, Mansour (Curtin University, 2011)
A review of the latest international grid codes shows that large wind power plants are stipulated to not only ride-through various fault conditions, but also exhibit adequate active and reactive power responses during the fault period in order to support the network stability. In particular, modern grid codes require wind power plants to: (1) ride-through various voltage sag and swell conditions, (2) inject reactive current into the grid during the fault period, and (3) attain swift active power restoration after the fault clearance. This thesis proposes a transient control scheme for DFIG-based wind power plants to comply with these requirements.In the first part of this thesis, the latest regulations enforced on large wind power plants are studied and compared. This study identifies the most stringent regulations defined by the international grid codes, to be further investigated in the following chapters. In the second part of this thesis, extensive simulation studies are carried out to examine the transient response of DFIG-based wind turbines under various symmetrical and asymmetrical fault conditions. Supplementary theoretical analyses are also presented to justify the observations made in the time-domain simulations results. For the first time, the impacts of phase-angle jump, voltage recovery process and sag parameters on the DFIG response are explored. The results of this study can assist researcher to identify the difficulties that hinder successful fault ride-through response of DFIG-based wind turbines, as requested by the international grid codes.In the third part of the thesis, an enhanced hysteresis-based current regulator (referred to as VBHCR) is proposed to be implemented in the rotor-side and grid-side converters of DFIG-based wind turbines. The main advantages of this current regulator are very fast transient response, simple control structure and insensitivity to the machine parameters variations. Simulation results show that on one hand the VBHCR has very good steady-state performance and on the other hand, it presents very fast/robust tracking response. Therefore, the DFIG equipped the proposed current regulator can fulfill the most stringent low-voltage ride-through requirements imposed by the international grid codes, i.e., those stipulated by the Australian grid code. In the fourth part of the thesis, a new hybrid current control scheme is introduced to enhance both low and high voltage ride-through capabilities of DFIG-based wind turbines. The proposed control scheme uses the standard PI current regulators under steady-state conditions but upon a voltage sag or swell occurrence, the supervisory control unit transfers the switching strategy of the rotor-side and grid-side converters to the hysteresis-based method. The VBHCR remains in action until the oscillation in the rotor current and dc-link voltage of DFIG suppress below the safety limit and then, the PI current regulator are activated through a re-initialization process.Finally, the conventional vector control scheme of DFIG-based wind power plants is modified to fulfill the regulations imposed on the active and reactive power responses of wind farms subject to various faults. New design strategies are suggested and their corresponding P-Q capability curves are thoroughly studied. Simulations results show that the proposed control scheme can meet the Australian regulations as the most demanding grid code. The best design strategy, with enhanced active and reactive power responses, permits the rotor-side and grid-side converters of DFIG to be temporarily overloaded during the fault period and also exploits the free capacity of the GSC to inject further reactive power to the grid. As a result, the active power generation of DFIG-based wind power plant can be retained during the fault period while its reactive power injection capacity of DFIG is also increased to further support the grid.